Electrochemical Behavior of Polypyrrole‐modified SnS2 for Use as Anode Material in Lithium‐Ion Batteries. Issue 11 (10th October 2016) - Luo, Dawei; Lin, Feng; Xiao, Wangdong; Li, Zhijun; Luo, Chaoyun; Li, Xue
Abstract : SnS2 /polypyrrole (PPy) composites were successfully synthesized by PPy modification of SnS2 via a simple and effective solvothermal and chemical method. The microstructure, morphology, electrical conductivity, PPy content, and electrochemical properties of these materials were characterized by X‐ray diffraction (XRD), scanning electron microscopy (SEM), four‐point probe technique, thermogavimetry (TG), and constant‐current charge/discharge tests, respectively. The results demonstrate that PPy is tightly coated on the 3D flower‐like SnS2 and that the conductivity of SnS2 /PPy composites can be greatly improved by the PPy modification. The electrochemical results indicate that PPy is not involved in the electrode reaction, but it can dramatically improve the reversible capacity and cyclic performance. The recharge capacity retention after 30 cycles remained at 523 mAh/g, which is significantly higher than that of SnS2 without modification by PPy. The better cycling performance compared to SnS2 nanoparticles should be due to the 3D nano‐flower‐like SnS2 particles and the modification of SnS2 by PPy. Abstract : SnS2 nanoparticles were self‐assembled into a uniform 3D flower‐like nanostructure, which consisted of a number of 2D nanosheets. In the case of SnS2 modified by polypyrrole (PPy), the image shows that the entire surface of SnS2 is coated with many PPy nanoparticles of size of 50 nm. The electrical conductivity of SnS2 /PPy is much higher than that of SnS2 .